The Effectiveness of Spiritual Counseling in Improving Holistic Well-Being in Female Students at An-Nahdloh Islamic Boarding School, Malaysia - Fifi Khoirul Fitriyah; Husni Hanafi; Hidayatul Khusnah; Sunanto; Winnuly; Tiyas Saputri; Rachma Aliefia Putri (UNUSA Press, 2026)
Female students in Islamic boarding schools often face academic, social, and psychological challenges that may affect their holistic well-being, highlighting the need for spiritually grounded interventions. The purpose of this study was to test the effectiveness of spiritual counseling in improving holistic well-being in female students at the An-Nahdloh Islamic Boarding School in Malaysia. This study involved 21 female students with a pre-experimental design without a control group. The results showed an increase in scores between before and after the intervention. Descriptive statistics showed that the average score increased by 8.94 points, from 64.44 to 72.94. These results indicate that spiritual counseling can help people feel better in general, but the degree of improvement varies from person to person. This study emphasizes the importance of implementing spiritual counseling in Islamic boarding schools to improve holistic well-being, including physical health, mental health, and financial health. Further research with a larger sample size, involving a control group, and longitudinal assessment is recommended to ensure the sustainability of the beneficial effects and its applicability across contexts.